Lords of finance : the bankers who broke the world - Ahamed, Liaquat (Penguin Press, 2009)
With penetrating insights for today, this vital history of the world economic collapse of the late 1920s offers unforgettable portraits of four men--Montagu Norman, Amile Moreau, Hjalmar Schacht, and Benjamin Strong--whose personal and professional actions as heads of their respective central banks changed the course of the twentieth century.